Anti-Microbiota Vaccines Modulate the Tick Microbiome in a Taxon-Specific Manner - Mateos-Hernández, Lourdes; Obregón, Dasiel; Wu-Chuang, Alejandra; Maye, Jennifer; Bornères, Jeremie; Versillé, Nicolas; de la Fuente, José; Díaz-Sánchez, Sandra; Bermúdez-Humarán, Luis G.; Torres-Maravilla, Edgar; Estrada-Peña, Agustín; Hodžić, Adnan; et al. (Frontiers in Immunology, 2021)
The lack of tools for the precise manipulation of the tick microbiome is currently a major limitation to achieve mechanistic insights into the tick microbiome. Anti-tick microbiota vaccines targeting keystone bacteria of the tick microbiota alter tick feeding, but their impact on the taxonomic and functional profiles of the tick microbiome has not been tested. In this study, we immunized a vertebrate host model (Mus musculus) with live bacteria vaccines targeting keystone (i.e., Escherichia-Shigella) or non-keystone (i.e., Leuconostoc) taxa of tick microbiota and tested the impact of bacterial-specific antibodies (Abs) on the structure and function of tick microbiota. We also investigated the effect of these anti-microbiota vaccines on mice gut microbiota composition. Our results showed that the tick microbiota of ticks fed on Escherichia coli-immunized mice had reduced Escherichia-Shigella abundance and lower species diversity compared to ticks fed on control mice immunized with a mock vaccine. Immunization against keystone bacteria restructured the hierarchy of nodes in co-occurrence networks and reduced the resistance of the bacterial network to taxa removal. High levels of E. coli-specific IgM and IgG were negatively correlated with the abundance of Escherichia-Shigella in tick microbiota. These effects were not observed when Leuconostoc was targeted with vaccination against Leuconostoc mesenteroides. Prediction of functional pathways in the tick microbiome using PICRUSt2 revealed that E. coli vaccination reduced the abundance of lysine degradation pathway in tick microbiome, a result validated by qPCR. In contrast, the gut microbiome of immunized mice showed no significant alterations in the diversity, composition and abundance of bacterial taxa. Our results demonstrated that anti-tick microbiota vaccines are a safe, specific and an easy-to-use tool for manipulation of vector microbiome. These results guide interventions for the control of tick infestations and pathogen infection/transmission.